Funny Ha Ha - Bujalski, Andrew; Grunsky, Matthias; Dollenmayer, Kate; Herlehy, Mark; Rudder, Christian (accent film, 2006)
Marnie (Kate Dollenmayer) is a 23-year-old Bostonite and, as "Funny Ha Ha" commences, is encountering that perennial post-university problem: what to do without school to lend structure, purpose and a social network to your life? The answer? Not a great deal. Well-educated yet unmotivated, the cast of Andrew Bujalski's debut drift through life and love, miscommunicating at every turn as only twenty-somethings can. Funny this ain't, more like cringe-worthily familiar ... With American indie cinema populated by slick studio-funded Sundance chasers, this is very much of the old school style. Low budget and intimate, perhaps to the point of belonging on the small screen rather than the cinema, its still an intelligent and unpretentious slice of life true American life. [www.bbc.co.uk]